Calidad de servicio en la decisión de compra en centros comerciales de Perú - Badajoz Ramos, Jesús Augusto (2023)
Objective: To describe the quality of service in the purchase decision of customers who go shopping to malls in Peru. Method: The type of research was descriptive and relational with a longitudinal non-experimental design. The population sample was made up of people who went to 47 shopping malls located in the capitals of the departments of Peru, where the sample size was determined by convenience, selecting 10 commercial establishments and choosing 206 customers. The applied technique was the survey and the instrument was the questionnaire. Results: For 60% of Peruvians, the quality of services offered by commercial establishments is of average level. Conclusion: Customers who visit shopping malls say that the quality of service influences their purchase decision, which is based on to the speed of attention, fulfillment of offers, staff agility and friendliness; an element that contributes on the brands’ willingness to improve their customer service.